Solar energy engineering : processes and systems - Kalogirou, Soteris (Elsevier/Academic Press, 2009)
With the threat of global warming, and the gradual depletion of petroleum supplies, solar electric power is rapidly becoming significant part of our energy mix. The range of solar cells spans different materials and different structures in the quest to extract maximum power from the device while keeping the cost to a minimum. Devices with efficiency exceeding 30% have been demonstrated in the laboratory. Solar Energy Engineering: Processes and Systems. Solar Energy Processes and Systems includes all areas of solar energy engineering. All subjects are presented from the fundamental level to the highest level of current research. The book includes subjects such as energy related environmental problems, solar collectors, solar water heating, solar space heating and cooling, industrial process heat, solar desalination, photovoltaics, solar thermal power systems and modelling of solar systems including the use of artificial intelligence systems in solar energy systems modelling and performance prediction. Environmental consequences of solar energy Solar desalination including indirect systems Modelling and performance prediction of solar energy systems Worked examples and cases studies.